Incentivising a career in older adult nursing: The views of student nurses. (12th July 2019) - Naughton, Corina; O'Shea, Katie L.; Hayes, Nicky
Abstract: Background and aim: Nurse vacancy rates in older adult services are disproportionately high compared to other areas of nursing. This is partly because few student nurses consider it an attractive career option once qualified due to perceptions of low‐status, strenuous nature of the work and impoverished care environments. The study aimed to explore students' perceptions of incentives that could counterbalance the barriers for new graduate nurses joining this speciality. Methods: A qualitative descriptive design using focus group interviews was carried out with six groups of student nurses ( n = 27) following completion of their acute care older adult placements in three hospitals. Data were analysed using thematic analysis. Results: The barriers from students' perspectives were constructed as a vicious cycle of staff shortages and inadequate resources that created impoverished environments leading to a dissonance between ideal and delivered care. Over one‐third of students were unlikely to consider a career in older adults nursing, but the remaining students could identify incentives that may tempt them. Four main themes and eight subthemes were identified: gerontological status and leadership (ward leadership; respected others); relational care (legitimising emotional support, care vs. cure goals); quality work environment (pay as recognition, 12‐hr shifts); and education‐career pathways (gerontological knowledge, career progression). Conclusion: Radical new approaches, based on student and nurse engagement, are required to incentivise a career in gerontological nursing. A combination of shorter and longer term strategies that include education‐career pathways, a focus on relation care, and improved work conditions including financial incentives should be trialled. Implications for practice: In terms of practice, addressing high nurse vacancy rates in older adult services that negaively impacts on patient outcomes requires a suite of incentives informed by 'what matters' to students and nurses working in the speciality.